A Gender Sensitive Research Guideline for Academia and Development - Sijapati, Dipendra Bikram; Mishra, Manamaya (Journal of Population and Development, 2024)
This paper focuses on gender based research in different development sectors of homogenous and divers society in Nepal. In social science, the gender-sensitive research gives equal importance to both the similarities and differences in the experiences and viewpoints of men and women. As a result, women's experiences and contributions have been overlooked in traditional research, leading to the omission of crucial aspects of a subject, underestimation of their significance, and the potential for misunderstandings. In recent times, however, there has been a growing recognition of gender as a significant variable in research. This article based on the objective to explain and highlight the existing variation of gender-sensitive research among development and environment sector. It analyses the provisions regarding research papers, articles, gender related books, Newspaper and seminar papers in academia. This paper widely covers concept, definition, theories, practice, situation, laws, policies and program in all gender sensitive research in all environmental and development levels.